Continuous Measurement of Breaks in Presence: Psychophysiology and Orienting Responses. Issue 3 (3rd July 2017) - Liebold, Benny; Brill, Michael; Pietschmann, Daniel; Schwab, Frank; Ohler, Peter
Abstract : Assessing presence using questionnaires can yield interesting insights into the user experience in virtual environments, but is also limited both in terms of reliability and validity. Breaks in presence (BIPs) are an interesting alternative, given that the researcher can assess them correctly. Prior studies on the psychophysiology of BIPs followed an exploratory approach by not providing a cognitive mechanism for BIPs and lacking in external validity. We argue that BIPs can be considered a special form of orienting responses involving both the real and the virtual world. In the first of the presented studies, we investigated which types of BIPs can be differentiated and to what degree they affect the user experience. In the second study, we modified a commercial video game by introducing the previously identified BIPs and recorded psychophysiological measurements. The results are in line with findings on orienting responses and should provide fertile ground for future research.